Comparison of the Effect of Adhesive Protocols and Light Curing Units on the Repair Bond Strength of Bulk Fill Composite Resins - Bilge, Kübra; İpek, İrem; Aşar, Enes Mustafa (Selcuk University, 2024)
Background: The aim of this study was to compare the shear bond strengths (SBS) of a microhybrid composite resin (CR) after repair with 3 different bulk fill CR using 2nd and 3rd generation light-emitting diode (LED) light devices and a universal adhesive applied with different protocols. Methods: 120 acrylic blocks, each with an open surface and a depth of 2 mm and a diameter of 6 mm, were filled with a microhybrid CR (Filtek Z250) and cured with an LED for 20 seconds. The samples were roughened for 5 seconds with a diamond fissure bur under water cooling and then subjected to 5,000 thermal cycles. A universal adhesive was applied to the prepared samples using two different protocols (total etch and self-etch), and samples were then filled with bulk fill CRs. Each bulk fill CR group was polymerized with 2nd and 3rd generation LED to form subgroups (n=10). The SBS values were recorded in MPa using a universal testing device. Results: The highest SBS values were obtained for the X-tra Fil group in total etch mode with polymerization using 3rd generation LED, while the lowest SBS values were found for Filtek One Bulk Fill group in self-etch mode with polymerization using the 3rd generation LED. In all groups, total etch mode yielded higher SBS values compared to self-etch mode. Conclusion: Different adhesive protocols and LCUs were found to affect the SBS values of bulk fill CRs during repair. © 2024, Selcuk University. All rights reserved.
Adeziv Protokollerinin ve Işıkla Sertleştirme Ünitelerinin Bulk Fill Kompozit Rezinlerin Tamir Bağlanma Dayanımı Üzerindeki Etkisinin Karşılaştırılması
Keywords: Adhesive Protocols; Bulk Fill Composite; Composite Repair; LED Units